Writing communities to (re-) engage faculty: The U See I Write Initiative - Ilona Sabine Yim; Nina Bandelj; Olga V Razorenova; Peiyi Wang (To Improve the Academy, 2023)
The COVID-19 pandemic has taken a toll on university faculty, unduly those from underrepresented groups, causing many faculty to disengage. Writing communities represent a promising tool to (re-)engage faculty and build an inclusive climate. As part of U See I Write, a faculty development initiative at the University of California, Irvine, we convened a series of monthly writing retreats between March and June of 2021, with between-retreat weekly writing sessions in smaller groups and an expectation to write daily for at least 30 minutes. In a diverse cohort of 34 faculty writers, program participation resulted in a significant increase in writing and work engagement. Similar initiatives at other institutions of higher education may prove successful in faculty (re-)engagement while also advancing faculty diversity.